A Factorial Analysis Study on Enzymatic Hydrolysis of Fiber Pressed Oil Palm Frond for Bioethanol Production. Issue 1 (March 2016) - Hashim, F S; Yussof, H W; Zahari, M A K M; Illias, R M; Rahman, R A
Abstract: Different technologies have been developed to for the conversion of lignocellulosic biomass to suitable fermentation substrates for bioethanol production. The enzymatic conversion of cellulose seems to be the most promising technology as it is highly specific and does not produce substantial amounts of unwanted byproducts. The effects of agitation speed, enzyme loading, temperature, pH and reaction time on the conversion of glucose from fiber pressed oil palm frond (FPOPF) for bioethanol production were screened by statistical analysis using response surface methodology (RSM). A half fraction two-level factorial analysis with five factors was selected for the experimental design to determine the best enzymatic conditions that produce maximum amount of glucose. FPOPF was pre-treated with alkaline prior to enzymatic hydrolysis. The enzymatic hydrolysis was performed using a commercial enzyme Cellic CTec2. From this study, the highest yield of glucose concentration was 9.736 g/L at 72 hours reaction time at 35 °C, pH 5.6, and 1.5% (w/v) of enzyme loading. The model obtained was significant with p-value <0.0001. It is suggested that this model had a maximum point which is likely to be the optimum point and possible for the optimization process.